THE IMPACT OF NON PERFORMING FINANCE (NPF), CAPITAL ADEQUACY RATIO (CAR), AND FINANCING DEPOSIT RATIO (FDR) TO RETURN ON ASSET (ROA) WITH DEPOSITOR FUNDS AS A MODERATING VARIABLE IN ISLAMIC BANKS - Ahmad Syifa (Universitas Pamulang, 2018)
Return On Asset (ROA) is one of the profitability indicators, this study aimed to know the effect of several internal factors; non performing financing (NPF), capital adequacy ratio (CAR) and financing to deposit ratio (FDR) and depositors funds to Return on Asset (ROA) in Islamic commercial bank in Indonesia. This study uses a sensus method from January 2009 to December 2015. Testing the hypothesis in this study is done by using multiple linier regression test analysis and test interaction moderated regression analysis (MRA) by using Statistical Package for the Social Sciences (SPSS) 23. Result of this research hypothesis show that in the model seen a significant influence on non performing financingand capital adequacy ratio to ROA with probability value (sig-t) 0,000 lowerthan 0,05, and the value of coefficient regression are -0,349 and -0,114 with negative score, it means that if NPF or CAR increase it can make ROAdecreasing. The result of third hypothesis shows that FDR has significantinfluence to ROA with probability value (sig-t) 0,019 lower than 0,05 and the value of coefficient regression is 0,028, it means that FDR has positive influence to ROA. This study also demonstrates the role of moderating variables that can be seen from the result of fourth until sixth hypothesis testing that significantly influence to ROA with probability value (sig-t) score 0,000, 0,022 and 0,003 lower than 0,05 and have coefficient regression value equal 1,029, 0,391 and 0,073 with positive score. Statistical of F test shows that Fcal equal to 24,053 while F table at 0,846, so that F cal > F table. It means that independent variablessuch as NPF, CAR, FDR, and DPK significantly influence to Return on Asset.